Encapsulation of caffeine into starch matrices: Bitterness evaluation and suppression mechanism - Shao, Miao; Li, Songnan; Tan, Chin Ping; Kraithong, Supaluck; Gao, Qing; Fu, Xiong; Zhang, Bin; Huang, Qiang (Elsevier, 2021)
In this study, caffeine (CA) was encapsulated into food-grade starch matrices, including swelled starch (SS), porous starch (PS), and V-type starch (VS). The bitterness of the microcapsules and suppression mechanisms were investigated using an electronic tongue, molecular dynamics (MD) simulation and the in vitro release kinetics of CA. All the CA-loaded microcapsules showed a lower bitterness intensity than the control. The MD results proved that the weak interactions between starch and CA resulted in a moderate CA release rate for SS-CA microcapsules. The PS-CA microcapsule presented the longest CA release, up to 40 min, whereas the VS-CA microcapsule completely released CA in 9 min. The CA release rate was found to be related to the microcapsule structure and rehydration properties. A low CA bitterness intensity could be attributed to a delay in the CA release rate and resistance to erosion of the microcapsules. The results of this work are valuable for improving starch-based microcapsules (oral-targeted drug-delivery systems) by suppressing the bitterness of alkaloid compounds.